Spatiotemporal variability of floodplain sediment and organic carbon retention in mountain streams of the Colorado Front Range - Sutfin, Nicholas A., author; Wohl, Ellen, advisor; Rathburn, Sara, committee member; Kampf, Stephanie, committee member; Borch, Thomas, committee member (Colorado State University. Libraries, 2016)
Organic carbon retention along river corridors is an important regulator of ecosystem processing and a growing body of research indicates that carbon storage in floodplains can be a significant component of the terrestrial carbon cycle. The first part of this dissertation reviews the literature on carbon storage along floodplains and presents a conceptual model that highlights how sediment accumulation on floodplains in cool, high-elevation mountainous environments could result in some of the highest organic carbon per area among rivers in diverse regions. Investigation of floodplain sediment along three study reaches of mountain streams in the Colorado Front Range indicates that depth-averaged mean soil organic carbon content of ~3 – 5 % is accurately estimated using systematic random sample at ~10 sampling locations. Sediment samples from an additional 21 study reaches indicate correlations between organic carbon content and soil moisture, sample depth, grain size, relative elevation of the floodplain surface, thickness of soil at the sampling location, and valley confinement. Older mean pooled-radiocarbon ages of charcoal in floodplain sediment at two study reaches above 2900 m (>1200 y BP) compared to ages at two study reaches below 2400 m (<700 y) suggest an elevational control on floodplain disturbance regime in the Front Range. Observations of floodplain disturbance, which occurred during regional floods in September 2013, indicated an exponential increase in the amount of floodplain area disturbed with decreasing elevation and increasing distance downstream. These results suggest potential correspondence with a previously documented shift in hydroclimatic disturbance regime at ~2300 m. Investigation of landscape-scale controls on organic carbon storage per area through comparisons of five different valley types (24 total study reaches) indicated that unconfined valleys may store more carbon per area and the dynamic environment in valley segments with multiple sub-parallel channels limits the capacity of floodplains to store sediment and associated carbon. The occurrence of multithread channels is dependent upon the presence of beavers or persistent logjams as biotic rivers of channel planform. Floodplains of single thread channels in unconfined valleys tend to be saturated and dominated by grasses and sedges, lacking the density of trees necessary to ensure continued recruitment of wood to the channel and into logjams. These results indicate that mountain streams are an important component of the terrestrial carbon cycle through carbon storage in unconfined single thread channels and ecosystem processing in more complex multithread channels.